Efficiency Analysis of Sea and Rail Intermodal in Merak - Tanjung Priok Freight Forwarding - Afiyah Kusuma; Muhammad Tohir (Siber Journal of Transportation and Logistics, 2025)
In the era of globalization and increasing national logistics needs, the efficiency of the transportation system is the main key in supporting the smooth distribution of goods. The Merak-Tanjung Priok route as one of Indonesia's strategic logistics corridors plays a vital role in connectivity between the islands of Java and Sumatra. This study aims to analyze the level of efficiency of the use of intermodal transportation systems, especially the combination of sea and rail modes in the distribution of goods across Merak-Tanjung Priok. Using a qualitative approach through literature study and secondary data, this study examines operational aspects, infrastructure, policies, and the contribution of logistics actors such as PT KAI Logistics (KALOG) and PT PELINDO. The results show that intermodality between sea and rail modes can improve shipping efficiency, reduce road congestion, and support sustainable logistics policies. The role of the government through regulations and incentives such as PP No. 8 of 2011 and PM No. 117 of 2016 also encourages more optimal modal integration. In conclusion, strengthening intermodal transportation based on sea and rail is an important strategy in reducing national logistics costs and increasing the competitiveness of Indonesia's distribution system.